2015
DOI: 10.1155/2015/418168
|View full text |Cite
|
Sign up to set email alerts
|

Modulation and Predictors of Periprosthetic Bone Mineral Density following Total Knee Arthroplasty

Abstract: Total knee arthroplasty (TKA) leads to a loss of periprosthetic bone mineral density (BMD). Great importance is attached to the prevention of periprosthetic bone loss with a view to ensuring a long service life of the prosthesis. In order to provide appropriate recommendations for preventive movement therapy measures to combat peri-implant bone loss, it is necessary to know the predictors of periprosthetic BMD. The aim of this study was (1) to determine the change of periprosthetic BMD of the femur and tibia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…The clinical outcome, ass quantified by the improvement in a functional score, was not associated with peri-prosthetic BMD change (11,12,25). A variable prosthesis-related stress-shielding and different patient's muscle mass could be possible explanations to these differences, as proposed Mau-Moeller et al after comparing DXA, muscle mass and strength ten days and three months after surgery in 23 patients undergoing TKA (26).…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…The clinical outcome, ass quantified by the improvement in a functional score, was not associated with peri-prosthetic BMD change (11,12,25). A variable prosthesis-related stress-shielding and different patient's muscle mass could be possible explanations to these differences, as proposed Mau-Moeller et al after comparing DXA, muscle mass and strength ten days and three months after surgery in 23 patients undergoing TKA (26).…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…In our HCS patient, the compromised bone status theoretically jeopardizes prosthetic osseointegration, substantiating cementation of the prosthesis at young age. In terms of preventive measures of peri-implant bone loss for patients undergoing TKA, moderate physical exercise can be recommended, as lean mass positively modulates periprosthetic BMD [ 16 ]. Finally, a close clinical and radiological follow-up should always be pursued in risk group patients undergoing orthopaedic surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…longitudinal study that reported the BMD of an area proximal to the superior border of the femoral components in 106 postmenopausal females. In a similarly designed study, Mau-Moeller et al [18] measured BMD three months postoperatively at the same femoral ROIs in 23 patients (65% male). Windisch et al [19] also measured supracondylar femur BMD prospectively in 50 patients at several time points in the first postoperative year.…”
Section: Discussionmentioning
confidence: 99%
“…Five of these studies were excluded as the absolute BMD could not be extracted. Details of the remaining studies included in the meta-analysis are shown in Table 1 (see Appendix for an in-depth summary of the studies) [10,[15][16][17][18][19][20][21][22][23][24][25][26][27]. Overall, BMD was reported for 547 patients on the operative side.…”
Section: Systematic Review Summarymentioning
confidence: 99%